Financial Performance Analysis Using the Du Pont System Method in Telecommunication Companies in Indonesia - Auliya Candi Pramana; Meigia Nidya Sari; Riska Franita (International Journal of Economics and Management, 2026)
Financial performance is one of the indicators used to assess a company's ability to generate profits, manage assets, and manage funding sources. This study analyzes the financial performance of PT. Telkom Indonesia, Tbk., PT. Indosat Ooredoo Hutchison, Tbk., and PT. XL Axiata, Tbk. during the 2020–2024 period using the Du Pont System method. The study uses a quantitative approach with a descriptive-comparative type. The data used are annual financial reports obtained through documentation and literature studies. The analysis was carried out using Net Profit Margin (NPM), Total Asset Turnover (TATO), and Equity Multiplier (EM) indicators. The results show that PT. Telkom Indonesia, Tbk. has a better level of profitability and asset utilization effectiveness than other companies. Meanwhile, PT. Indosat Ooredoo Hutchison, Tbk. recorded the highest Equity Multiplier value, indicating greater use of debt-based funding. Based on a comparison of these three indicators, PT. Telkom Indonesia, Tbk. showed the best financial performance during the study period.